Cyber denial, deception and counter deception : a framework for supporting active cyber defense /: a framework for supporting active cyber defense. (2015) - Heckman, Kristin E; Stech, Frank J; Thomas, Roshan K; Schmoker, Ben; Tsow, Alexander W
No abstract available